Hamlet : Prince of Denmark [Hamlet anglicky] - Shakespeare, William, 1564-1616; Macaw Books (Leicester : Sweet Cherry Publishing : [distributor] Sweet Cherry Publishing, 2020)
"Hamlet, Prince of Denmark" is one of the most popular tragedies of William Shakespeare. It tells the sad story of Hamlet, the Prince of Denmark, who, upon his father´s death, returns from Wittenberg to discover the evil plot of his Uncle Claudius and his mother, Queen Gertrude. The play is focused around how Hamlet learns the truth about his father´s death and seeks revenge.
A short narrative version of the play has been suitably adapted to help to introduce the play to young readers.
Keywords: Children's stories; čítam si sám (7+); cudzojazyčná literatúra